2021
DOI: 10.1093/neuonc/noab243
|View full text |Cite
|
Sign up to set email alerts
|

Trabectedin for recurrent WHO grade 2 or 3 meningioma: A randomized phase II study of the EORTC Brain Tumor Group (EORTC-1320-BTG)

Abstract: Background No systemic treatment has been established for meningioma progressing after local therapies. Methods This randomized, multicenter, open-label, phase 2 study included adult patients with recurrent WHO grade 2 or 3 meningioma. Patients were 2:1 randomly assigned to intravenous trabectedin (1.5 mg/m 2 every three weeks) or local standard of care (LOC). The primary endpoint was progression-free survival (PFS). Secondar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Trabectedin, a chemotherapeutic agent used to treat advanced sarcoma, exhibited therapeutic activity for grade 2/3 meningioma cells in vitro [ 30 ]. However, a prospective randomized phase II clinical trial on patients with recurrent grade 2 or 3 meningiomas showed that trabectedin did not improve progression-free survival or overall survival [ 4 ]. A prospective phase II study on nivolumab, a programmed death 1 blocking antibody, among patients with grade 2/3 meningioma demonstrated that it failed to improve six-month progression-free survival; however, a minor subset of patients characterized by a high tumor mutation burden benefited from the treatment [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trabectedin, a chemotherapeutic agent used to treat advanced sarcoma, exhibited therapeutic activity for grade 2/3 meningioma cells in vitro [ 30 ]. However, a prospective randomized phase II clinical trial on patients with recurrent grade 2 or 3 meningiomas showed that trabectedin did not improve progression-free survival or overall survival [ 4 ]. A prospective phase II study on nivolumab, a programmed death 1 blocking antibody, among patients with grade 2/3 meningioma demonstrated that it failed to improve six-month progression-free survival; however, a minor subset of patients characterized by a high tumor mutation burden benefited from the treatment [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…A number of chemotherapeutic reagents have been applied to the treatment of patients with meningioma; however, the efficacy of these reagents, including trabectedin, which was considered promising for meningioma, has mostly been small [ 3 , 4 ]. On the other hand, recent advances in our understanding of genomic alterations in meningioma have resulted in the introduction of potential therapeutic targets, such as mammalian target of rapamycin (mTOR), vascular endothelial growth factor receptor, the hedgehog pathway, focal adhesion kinase, AKT, and cyclin-dependent kinase [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy of cytotoxic agents such as hydroxyurea [12][13][14][15], irinotecan [16], temozolomide [17,18], or combination regimens such as vincristine, adriamycin and cyclophosphamide (VAC) [19] has been evaluated, with overall limited efficacy (Table 1). Whereas the DNA-intercalating agent trabectedin has shown promising activity in vitro and in one heavily pretreated patient [20], a prospective randomized phase 2 trial (EORTC 1320) failed to meet its primary endpoint, with no difference to physician's choice in terms of antitumoral activity but significantly higher toxicity [21].…”
Section: Systemic Treatment In Meningiomathe Status Quomentioning
confidence: 99%
“…Other previously studied drugs include imatinib, erlotinib and gefitinib, with no relevant clinical activity [38][39][40][41]. These results which mainly stem from retrospective or small prospective studies could be substantiated in exploratory analyses of the EORTC 1320 study, where physician's choice was included as a control arm [21]. Control treatments included the cytotoxic compounds hydroxyurea, vincristine, cyclophosphamide, doxorubicin as well as bevacizumab and somatostatin analogs.…”
Section: Systemic Treatment In Meningiomathe Status Quomentioning
confidence: 99%
“…140) However, in the EORTC Brain Tumor Group's randomized phase II trial (EORTC-1320-BTG), trabectedin did not improve overall survival in recurrent WHO grades 2 and 3 meningiomas. 141)…”
Section: Trabectedinmentioning
confidence: 99%